Jak żyje i co myśli o swoim zdrowiu młodzież szkolna? - Izdebski, Zbigniew (1956- ) - red.; Mazur, Joanna - red. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The report presents the results of a survey conducted online among students in the Lubusz Voivodeship in April 2024 by the Department of Humanization of Medicine and Sexology at the University of Zielona Góra. The study covered 9,411 students from grade VII of primary schools and grades I and III of secondary schools, representing approximately 30% of the population in these age groups. The questionnaire contained 53 questions from 11 areas and the KIDSCREEN-27 module.
Keywords: młodzież; zachowania zdrowotne; zdrowie; profilaktyka; edukacja zdrowotna; województwo lubuskie; adolescents; health behaviours; health; prevention; health education; Lubusz Voivodeship